THE LEXICAL AND GRAMMATICAL MEANINGS OF THE RUSSIAN VERB AND THE SEMANTIC FIELD OF CAUSATION - Gulnara, Distanova; Vlada, Nikitina; Elena, Gvozdeva (Revista Inclusiones, 2020)
The article presents a theoretical analysis of the causal category of Russian verbs. It is proved that casual verbs have specific semantics that unite different situations. However, the complexity of the Russian language system studying Is associated with the indefinite status of Russian verbs causation